On my country and the world - Gorbachev, Mikhail Sergeevich, 1931-2022. (New York : Columbia University Press, 2000)
"Drawing on his own experience and rich archival material, Mikhail Gorbachev speaks his mind not only on a range of subjects concerning Russia's past, present, and future place in the world but also on the emerging global realities of the twenty-first century. In this book Gorbachev discusses the October Revolution, the Cold War, key figures such as Lenin, Stalin, and Yeltsin, nuclear proliferation, and NATO's bombing of Yugoslavia."--Jacket
The October Revolution: Its Sense and Significance -- A Blunder of History, Accident, or Necessity? -- Was Socialism Built in the Soviet Union? -- Let's Not Oversimplify! A Balance Sheet of the Soviet Years -- October and the World -- One More Balance Sheet: Something Worth Thinking About -- October and Perestroika -- Does Socialism Have a Future? -- The Union Could Have Been Preserved -- A Tragic Turn of Events -- Tbilisi ... Baku ... Vilnius -- Toward a New Union Treaty -- Referendum on the Union -- The Coup: A Stab in the Back--and the Intrigues of Yeltsin -- The Belovezh Accord: Dissolution of the USSR -- What Lies Ahead? -- The New Thinking: Yesterday, Today, and Tomorrow -- The Sources of the New Thinking -- The Very First Steps -- The Conception (1985-1991) -- Overcoming the Cold War -- The Transitional World Order -- The New Thinking in the Post-Confrontational World -- The Challenge of Globalization -- The Challenge of Diversity -- The Challenge of Global Problems -- The Challenge of Power Politics -- The Challenge of Democracy -- The Challenge of Universal Human Values -- The Beginning of History?
Includes index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Gorbachev, Mikhail Sergeevich, -- 1931-2022 -- Political and social views; Gorbachev, Mikhail Sergeevich, -- 1931-2022; Razmyshleniia o proshlom i budushchem; Soviet Union -- History -- Philosophy; Russia (Federation) -- History -- 1991- -- Philosophy; World politics -- 1989-; URSS -- Histoire -- Philosophie; Russie -- Histoire -- 1991- -- Philosophie; Politique mondiale -- 1989-; HISTORY; HISTORY -- Europe -- Russia & the Former Soviet Union; Philosophy; Political and social views; World politics; Russia (Federation); Soviet Union; Politiek; Communisme; Internationale betrekkingen; World politics -- 1989; Soviet Union -- History -- Philosophy; Russia (Federation) -- History -- 1991 -- Philosophy; Since 1989; History